On a General Notion of Transformation for Multiagent Systems and its Implementation - Pfalzgraf, Jochen; Soboll, Thomas (Electronic Communications of the EASST, 2009)
The focus of this contribution is on the construction of a transformation system for Multiagent Systems (MAS) based on categorical notions. Based on former work on the categorical modeling of MAS the category MAS of all Multiagent Systems is introduced. A transformation system over this category is established using the Double Pushout Approach. For illustration we present a simple example. First steps of implementational work are described.